The effects of personal green spaces on human’s mental health and anxiety symptoms during COVID-19: The case of apartment residents in Tehran - Khaledi, Hanieh Jafari; Faizi, Mohsen; Khakzand, Mehdi (Frontiers in Built Environment, 2022)
The governments implemented social distancing and isolation with the spread of COVID-19. However, these ways efficiently prevent coronavirus transmission, but they caused unprecedented changes in most people’s day-to-day lives. One of the concerns is mental health, and many experts are concerned about the tsunami of mental illnesses during and after coronavirus. Being exposed to nature has an efficient role in mental health. Under pandemic conditions, people reduced their outdoor activities, but personal green spaces are still available. This research assessed the impact of these spaces as an alternative to public green spaces and their benefits during COVID-19 on mental health and generalized anxiety disorder. Accordingly, by designing an online self-administered questionnaire, a total of 700 residents of Tehran apartments were evaluated. A structural equation model was created. The results demonstrate that using personal green spaces has a negative correlation and significant impact on general mental health and generalized anxiety disorder. It also plays a more substantial role in reducing depression than its role in reducing anxiety among individuals. Therefore, maximum land use policies should be reviewed. Also, green spaces should be given more attention in post-COVID designs on a macro-scale to a small scale.